2016
DOI: 10.1016/j.jff.2016.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of lyophilised black raspberries and combination of celecoxib and PBIT in prevention of carcinogen-induced oesophageal cancer in rats

Abstract: The objective of this study was to compare the efficacy and mechanism of lyophilized black raspberries (BRB) versus the combination of celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, and S,S′-1,4-phenylene-bis(1,2-ethanediyl)bis-isothiourea (PBIT), a selective inducible nitric oxide synthase (iNOS) inhibitor in inhibition of carcinogen-induced esophageal squamous cell carcinoma in rats. Our data indicated that tumor multiplicity and histologic grade of esophageal precancerous lesions were reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Our previous study showed the significant chemoprevention effects of strawberry in CRC mouse model and its role in inflammation inhibition [18]. We also demonstrate that black raspberry inhibits oxidative stress, the inflammation mediators, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) and exhibits superior anti-cancer effects than inhibitors of COX-2 and iNOS in an animal model [21,22]. In this review, we summarize the roles of strawberry, black raspberry, and their polyphenol components on CRC chemoprevention in IBD.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous study showed the significant chemoprevention effects of strawberry in CRC mouse model and its role in inflammation inhibition [18]. We also demonstrate that black raspberry inhibits oxidative stress, the inflammation mediators, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) and exhibits superior anti-cancer effects than inhibitors of COX-2 and iNOS in an animal model [21,22]. In this review, we summarize the roles of strawberry, black raspberry, and their polyphenol components on CRC chemoprevention in IBD.…”
Section: Introductionmentioning
confidence: 92%
“…Anthocyanins are flavonoid compounds that are responsible for the colors of most fruits and vegetables, and they contribute to the protective effects of fruits and vegetables against chronic diseases and cancer (Figure 2). According to our previous studies, anthocyanins are the main components in strawberry and black raspberry (Table 2) [18,22]. Among the anthocyanins, cyanidin rutinoside is the most abundant in black raspberry, whereas pelargonidin glucoside is the most abundant in strawberry.…”
Section: Chemoprevention Of Colorectal Cancer In Inflammatory Bowementioning
confidence: 99%
“…Dracorhodin perchlorate (DP), a synthetic analog of the anthocyanin red pigment dracorhodin, exerts various pharmacological effects, including anti-cancer activity in human ESCC cells due to G 2 /M phase cell cycle arrest through upregulation of p21 and p27, and downregulation of cyclin B1 and Cdc2 [208]. Importantly, anthocyanins are superior to the combination of celecoxib, a selective COX-2 inhibitor, and S,S'-1,4-phenylene-bis(1,2-ethanediyl)bis-isothiourea (PBIT), a selective iNOS inhibitor, in suppressing carcinogen-induced ESCC in rats [209].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…They were frozen and stored at -20ºC. Before the analysis they were defrosted, dried at 40ºC and grounded on a domestic mill [7].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Raspberries are known for their antitumoral, antibacterial, antiinfamatory [6,7] and antioxidant activities [8].…”
Section: Introductionmentioning
confidence: 99%